Isolation and Diagnosis of Fungi Which Producing Aflatoxin B1in Chips in Local and Imported Markets Najaf Province - R. A. Sahib (Journal of Global Pharma Technology, 2018)
This study included isolating and diagnosing contaminated fungi from some local and imported chipsin Najaf Province,and to detect their ability to produce aflatoxin B1. The results showed that highest percentageof visible fungi namely are Aspergillusflavus, A. niger, A. glaucus, Alterneria sp., Fusarium sp. and A. terreusith ratio are (100, 95, 92,80, 75, 5.7) % respectively in Wejoh chips and these fungi appeared in all types of chips under study. The results of the frequency of the same fungi in the wejoh chips are (80,70, 68, 52, 50,2) % respectively.A.flavus is more visible and frequently in thesame types of chips,and preferable sabouraud dextrose (agar,broth) medium to growth. Primary result proved that A. flavus producing aflatoxin B1in Thinlayerchromatography (TLC) which appear blue spot of aflatoxin B1 with rate of flow (RF) is 56 % under UV light expose with wavelength of (365 nm).High performance liquid chromatography (HPLC) results show that retention time or major peak of standard aflatoxin B1 located at 10.54 minutes, while a filter extract of A. flavusis10.75 which identifies with aflatoxin B1 standardwhich located in the same area.Keywords: Chips, A. flavus, Aflatoxin B1, SEM, TLC, HPLC.